The Acquisition of WH Question by EFL Students' Learning English as a Foreign Language - Andriyani, Ellen, Prof. Dr. Endang Fauziati, M. Hum, Muamaroh, Ph. D (2016)
This study aims to describe the acquisition of wh question by EFL students' learning English as a Foreign Language. Especially to describe the patterns of question written by the students of the seventh and the ninth grade students of junior high school and the eleventh grade students of senior high school. Then the development patterns of question between three of them. The method of this study was qualitative and cross-sectional study. The riter analyzed the patterns of question written by the seventh grade, the ninth grade, and the eleventh grade students. Then the writer combined the theory by Dulay et al (1982: 128) and Freeman-Larsen (1991: 93). The writer found that there are three stages of the development pattern of question: Stage two: Uninverted WH (+/- aux.). "wh question + S + verb". Step three: The early auxiliaries. "wh question + unanalyzed to be + S + verb". Stage four: The learner reaches the full target system. "wh question + analyzed to be + S + verb".